Oath and honor : a memoir and a warning - Cheney, Liz, 1966- (Little, Brown and Company, 2023)
"A gripping first-hand account from inside the halls of Congress as Donald Trump and his enablers betrayed the American people and the Constitution--leading to the violent attack on our Capitol on January 6th, 2021--by the House Republican leader who dared to stand up to it. In the aftermath of the 2020 presidential election, Donald Trump and many around him, including certain other elected Republican officials, intentionally breached their oath to the they ignored the rulings of dozens of courts, plotted to overturn a lawful election, and provoked a violent attack on our Capitol. Liz Cheney, one of the few Republican officials to take a stand against these efforts, witnessed the attack first-hand, and then helped lead the Congressional Select Committee investigation into how it happened. In Oath and Honor , she tells the story of this perilous moment in our history, those who helped Trump spread the stolen election lie, those whose actions preserved our constitutional framework, and the risks we still face"--